Features of Thymus Gland Structure in Children Immune System Dependence on Thymus (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
A huge mystery of the biology of medicine (primarily immunology) and in particular pediatrics is the thymus gland (thymus). This is despite the fact that he paid the closest attention of researchers for 4 or more centuries. Only in the 20th century did the attitude of scientists to the organ as a generator and regulator of immune responses, a participant in the production of many populations of immunocompetent cells, and so on, be determined. Thymus and is currently seen as a derivative of the immune system and, to a greater extent, as its central organ. Infectious diseases, systemic autoimmune diseases, oncology, the problem of tissue incompatibility determine the life expectancy of a person and therefore the scientific interest in the topic of studying the functions of the immune system and its central organ-thymus gland is clear. The difficulty of studying lies in the huge number of integral connections of the thymus gland with other components of the immune system, neuroendocrine, hematopoietic and connective tissue, organs (and cells) providing barrier function, etc. To isolate functions directly concerning the thymus from this continuum is a high-tech task of extreme complexity. The interest of pediatricians in this area of  knowledge is associated with a certain understanding of human ontogenesis from birth to old age, where the thymus plays a major role in the antenatal and early postnatal period. The task of this review, if possible, to isolate and focus on some, in our opinion, "white spots" of an ambiguous assessment of the functions attributed to the thymus gland, its structures and cellular pulp.